The association between patterns of trauma exposure, family dysfunction, and psychopathology among adolescent females with depressive symptoms from low-income contexts - Alto, Michelle E. (Child maltreatment, 2023)
Distinguishing profiles of trauma exposure among low-income adolescent females with depressive symptoms is important for understanding comorbidity, family relationships, and treatment. Specifically, child maltreatment is essential to examine in comparison to other traumas. Participants included 170 adolescent females (65.3% Black; 21.2% White; 13.5% other race; 14.1% Latina/x) with depressive symptoms and their primary caregiver from low-income families. Latent class analysis (LCA) identified three trauma classes. Probabilities of endorsing different subtypes of maltreatment (physical abuse, physical neglect, emotional abuse, emotional neglect, and sexual abuse), number of subtypes of maltreatment, and non-maltreatment traumas (accident, experiencing or witnessing physical assault, death or injury of loved one, medical trauma) varied among groups. Higher levels of family dysfunction and traumatic stress symptoms were reported in both classes with maltreatment exposure as compared to the class with only non-maltreatment trauma exposure. Findings have implications for family-focused interventions for maltreated adolescent females with depressive symptoms from low-income contexts.